EVALUASI PENYIMPANAN OBAT DI APOTEK MAYANG - Amraini Amelia (Program Studi Farmasi UNAJA, 2022)
Background: The storage of the drug must be such that it does not pose a hazard. The existence of a drug arrangement that is not appropriate and regular as well as a narrow spatial arrangement makes the drug located inappropriately based on its place and distribution. The negative impact caused by damaged drugs is not only on the patient, but also on the pharmacy itself. Objective: This study aims to evaluate the drug storage system at Apotek Mayang based on the technical guidelines for pharmaceutical standards at the Pharmacy in 2019. Method: This research is a descriptive observational study, which aims to look at the drug storage system at Apotek Mayang. Results: Based on the results of the research conducted, it can be concluded that drug storage at Apotek Mayang is fully in accordance with the Technical Guidelines for Pharmaceutical Service Standards at Pharmacies in 2019, it can be seen from the percentage results of 86.95% which are appropriate. Conclusion: Drug storage at Apotek Mayang is almost completely in accordance with the technical guidelines for pharmaceutical standards in pharmacies in 2019. Conclusion: Drug storage at Apotek Mayang is almost completely in accordance with the technical guidelines for pharmaceutical standards in pharmacies in 2019.